O papel dos burocratas de nível da rua na implementação de políticas intersetoriais: articulação dos programas sociais e de acesso à água no Semiárido brasileiro - Patrícia S. Mesquita; Carolina Milhorance; Louise Cavalcante (Confins)
Since the 2000s, policies promoting decentralized access to water in Brazil’s semiarid region have been established as components of a broader strategy to reduce poverty and food insecurity. Despite its intersectoral and integrated approach with social policies, the multiplication of institutional arrangements and programs with distinct logics of implementation has increased their level of fragmentation. This article analyses the process of coordination of the Cisterns Program with other rural poverty reduction programs, identifying factors that contribute to its programmatic and institutional integration. The study analyzes existing coordination mechanisms at the national level, and it innovates by discussing the informal role of municipal managers and providers of technical assistance in program coordination during the implementation process. Primary and secondary data were mobilized, including interviews with federal and local managers and actors involved in program implementation.